NOMINA VERBA (MASHDAR) SAMAâIY FIâIL TSULATSI MUJARRAD Kajian Morfologi - , KHODIJAH, Prof. Dr. Syamsul Hadi, SU.,MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis is a study related to the noun verb (mashdar) samÄ'Ä«y fi'il tsulatsi mujarrad (verb triliteral denuded). This study focuses on the concepts of theoretical discussion of noun verb samÄ'Ä«y in Arabic with patterns that exist. For that, in looking at the object of this study, the approach used is approach to morphology. This approach was used to examine the structures of the noun verb samÄ'Ä«y fi'il tsulatsi mujarrad. In an effort to find the methods in the data analysis stage, the research method using intralingual padan. This method is used to see the structures of the noun verb samÄ'Ä«y fi'il tsulatsi mujarrad. This research focused on the system of noun morphology variables that include three main parts, namely the noun verb morphology, samÄ'Ä«y characters, different types, and the process of morfologis. From this research produced a few main points, which are, first: first, the character formation of nouns verbs in fi'il tsulatsi mujarrad based on root system and pattern. Integrities roots and patterns will form the whole noun lexical and grammatical meanings. Second, the Noun verb in fi'il tsulatsi mujarrad divided into two nouns verbs qiyÄsiy and nouns verbs samÄ'iy. Noun verb samÄ'iy being the main focus of morphological processes. These nouns are of two types, namely, intransitive (lazim) and transitive (muta'addi). Third, the noun the verb samÄ'iy is used in two contexts, i.e. the manufacture or use of a form of words that is based on what is commonly used and heard directly from the rated Arabic expert, and the use of methods of standardization of rules through the search process, listening, recording directly from the Arabic (fushahaâ).